Is a picture-perfect thrombectomy necessary in acute ischemic stroke?. (16th February 2021) - Chen, Ching-Jen; Chalhoub, Reda; Ding, Dale; Kumar, Jeyan S; Ironside, Natasha; Kellogg, Ryan T; Worrall, Bradford B; Southerland, Andrew M; Jabbour, Pascal; Wolfe, Stacey Q; Arthur, Adam S; Goyal, Nitin; et al.
Abstract : Background: The benefit of complete reperfusion (modified Thrombolysis in Cerebral Infarction (mTICI) 3) over near-complete reperfusion (≥90%, mTICI 2c) remains unclear. The goal of this study is to compare clinical outcomes between mechanical thrombectomy (MT)-treated stroke patients with mTICI 2c versus 3. Methods: This is a retrospective study from the Stroke Thrombectomy and Aneurysm Registry (STAR) comprising 33 centers. Adults with anterior circulation arterial vessel occlusion who underwent MT yielding mTICI 2c or mTICI 3 reperfusion were included. Patients were categorized based on reperfusion grade achieved. Primary outcome was modified Rankin Scale (mRS) 0–2 at 90 days. Secondary outcomes were mRS scores at discharge and 90 days, National Institutes of Health Stroke Scale score at discharge, procedure-related complications, and symptomatic intracerebral hemorrhage. Results: The unmatched mTICI 2c and mTICI 3 cohorts comprised 519 and 1923 patients, respectively. There was no difference in primary (42.4% vs 45.1%; p=0.264) or secondary outcomes between the unmatched cohorts. Reperfusion status (mTICI 2c vs 3) was also not predictive of the primary outcome in non-imputed and imputed multivariable models. The matched cohorts each comprised 191 patients. Primary (39.8% vs 47.6%; p=0.122) and secondary outcomes were also similar between the matched cohorts, except the 90-day mRS which was lower in the matched mTICI 3 cohort (p=0.049). There were increased odds of the primary outcome with mTICI 3 in patients with baseline mRS ≥2 (36% vs 7.7%; p=0.011; pinteraction =0.014) and a history of stroke (42.3% vs 15.4%; p=0.027; pinteraction =0.041). Conclusions: Complete and near-complete reperfusion after MT appear to confer comparable outcomes in patients with acute stroke.